2018
DOI: 10.3389/fpls.2018.01817
|View full text |Cite
|
Sign up to set email alerts
|

Rice Mutants Lacking Starch Synthase I or Branching Enzyme IIb Activity Altered Starch Biosynthetic Protein Complexes

Abstract: Amylopectin, the major component of starch, is synthesized by synergistic activity of multiple isozymes of starch synthases (SSs) and branching enzymes (BEs). The frequency and length of amylopectin branches determine the functionality of starch. In the rice endosperm, BEIIb generates short side chains of amylopectin and SSI elongates those branches, which can be further elongated by SSIIa. Absence of these enzymes greatly affects amylopectin structure. SSI, SSIIa, and BEIIb associate with each other and with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(63 citation statements)
references
References 61 publications
3
57
2
1
Order By: Relevance
“…Is there any scenario explaining the different contribution of BEIIa to amylopectin biosynthesis either in the presence or absence of BEIIb? As already mentioned above, Crofts et al (2018) recently reported that the BEIIb protein must play an important role in the formation of several kinds of protein complexes among starch biosynthetic isozymes in rice endosperms using a japonica -type WT rice cultivar Nipponbare and EM10. For example, BEIIb forms a protein complex among BEI, SSI, SSIIa, and SSIIIa.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Is there any scenario explaining the different contribution of BEIIa to amylopectin biosynthesis either in the presence or absence of BEIIb? As already mentioned above, Crofts et al (2018) recently reported that the BEIIb protein must play an important role in the formation of several kinds of protein complexes among starch biosynthetic isozymes in rice endosperms using a japonica -type WT rice cultivar Nipponbare and EM10. For example, BEIIb forms a protein complex among BEI, SSI, SSIIa, and SSIIIa.…”
Section: Discussionmentioning
confidence: 82%
“…It is known that rice BEIIb has a very strict chain-length specificity because it synthesizes almost exclusively the DP7 and DP6 chains by attacking the DP12-14 chains ( Nakamura et al, 2010 ; Sawada et al, 2014 ). It can be also pointed out the rice endosperm BEIIb plays a key role in the formation of enzyme-enzyme complexes ( Crofts et al, 2015 , 2017 , 2018 ). These properties of BEIIb might be related to its role during the formation of cluster chains and hence BEIIb could affect profoundly the crystalline characteristics and physiochemical properties of starch granules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been reported that one of the recombinant OsBEI, OsBEIIa, or OsBEIIb interacts with recombinant starch synthase I from rice under in vitro conditions to produce branched α-glucan (96). Alternative protein complexes are also found in rice mutants lacking BEIIb activity or starch synthase isozyme I, IIa, and/or IIIa activities (97,98). (Fig.…”
Section: E Post-translational Modification and Protein-protein Intermentioning
confidence: 99%
“…The amylose is synthesized by granule-bound starch synthase I, and the amylopectin is synthesized by the combined actions of soluble starch synthase, starch branching enzyme, and starch debranching enzyme. Mutants with a mutation or expression change of starch-synthesis-related enzyme genes can alter starch components [24,25].…”
Section: Starch Components In Brown Kernels Of Rice Mutantsmentioning
confidence: 99%